1995
DOI: 10.1071/ea9951069
|View full text |Cite
|
Sign up to set email alerts
|

Performance of crossbred progeny of Trangie Fertility Merino and Booroola Merino rams and Poll Dorset ewes. 1. Lamb birth weight, survival and growth

Abstract: Merino rams of the Trangie Fertility and Booroola strains were joined to Poll Dorset ewes in single sire mating groups over 3 years. Forty sires produced a total of 1250 lambs in 885 litters from 451 ewes. Lamb birth weight averaged 4.1 kg, 80.8% of lambs survived to 3 days of age and growth rates to weaning (mean 93 days) averaged 289 g/day. Lambs with Trangie Fertility sires grew 15 g/day faster and were 1.3 kg heavier at weaning than those lambs with Booroola sires (P<0.001). There were no effects of sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
2
10
2
1
Order By: Relevance
“…In the same way, a higher proportion of the lightest lambs at birth was born as triplets compared with the proportion of triplets in the flocks. Similar results were found by Hall et al (1995), Holst et al (2002) and Christley et al (2003). They showed that birth weight had a non-linear relationship with hazard of mortality, with both lighter and heavier lambs at greater risk.…”
Section: Discussionsupporting
confidence: 80%
“…In the same way, a higher proportion of the lightest lambs at birth was born as triplets compared with the proportion of triplets in the flocks. Similar results were found by Hall et al (1995), Holst et al (2002) and Christley et al (2003). They showed that birth weight had a non-linear relationship with hazard of mortality, with both lighter and heavier lambs at greater risk.…”
Section: Discussionsupporting
confidence: 80%
“…A significant h² estimate was computed in the present study. This estimate accorded with a value of 0.11 reported for crossbred lambs by Hall et al (1995). It was, however, higher than corresponding estimates of 0.01 recently reported by Lopez-Villalobos and Garrick (1999) and that of 0.01 to 0.03 reported by Morris et al (2000).…”
Section: Discussioncontrasting
confidence: 51%
“…It was, however, higher than corresponding estimates of 0.01 recently reported by Lopez-Villalobos and Garrick (1999) and that of 0.01 to 0.03 reported by Morris et al (2000). Hall et al (1995) reported a litter variance -this could also be expressed as a maternal temporary environmental effect (Lewis & Beatson 1999) -amounting to 19% of the total phenotypic variance. This estimate differs from the c² estimate in the present study in the sense that it involved lambs born in the same litter in fecund Booroola crossbred ewes.…”
Section: Discussioncontrasting
confidence: 50%
“…When dystocia occurred, the risk of lamb loss increases more in ewes with single lambs than in ewes with larger litters (Holmøy et al, 2014). Dystocia is reported as a more frequent cause of death in single lambs than in lambs in larger litters (Dalton et al, 1980;Hall et al, 1995). In cases of dystocia associated with litters of multiples, often due to malpresentation of lambs (Speijers et al, 2010), successful obstetric delivery may be achieved with less trauma because of the smaller foetuses.…”
Section: Discussionmentioning
confidence: 99%